Some questions regarding the consecrated life in the oriental canonical legislation - TANASIYCHUK, ANDRIY (Prawo Kanoniczne, 2014)
Title XII of the Codex Canonum Ecclesiarum Orientalium dedicated to the religious institutes in the oriental catholic traditions is made up of four chapters. The first chapter begins with some general preliminary canons (Art. I, cc. 410-432) on monks and other religious. These norms are to be born in mind while dealing specifically with monasteries, orders and congregations. Canonical questions regarding monasteries as such are treated in the second article (cc. 433-503), while the third refers to orders and congregations. Another important aspect of the oriental law on religious institutes is the typology of the forms of the consecrated life. This is quite different from the Latin legislation. In fact, the CCEO identifies five institutional and three individual kinds of the consecrated life, while the CIC simply distinguishes between religious and secular institutes.